Pengaruh Spesialisasi Auditor, Opini Audit, dan Pergantian Auditor Terhadap Audit Delay: Studi Empiris pada Emiten Sektor Transportasi dan Logistik Tahun 2020-2023 - Bella Nugraheni; Istianingsih Sastrodiharjo; Aloysius Harry Mukti (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This research aims to examie auditor spelization, audit opinion,auditor switching on audit delay. The population in this research is emiten sector transportation and logistic Stock Exchange 2020-2023. The variables used in this research are Audit Delay as the dependent variable; Auditor Spelization, Audit Opinion, And Auditor Switching as the independent variable. The sampling technique used was the purposive sampling method and a sample of 23 companies and 91 sample. The analysis methods usedare Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test. The research result show that Auditor Spelization has a negative effect on Audit Delay. Audit Opinion has a negative effect on Audit Delay. Auditor Switching has a positive effect on Audit Delay.